2016
DOI: 10.3174/ajnr.a4638
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lesion Detection by Using Axial T2-Weighted MRI with Full Spinal Cord Coverage in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:Identification of lesions in specific locations gains importance in multiple sclerosis imaging diagnostic criteria. In clinical routine, axial scans are usually exclusively obtained to depict the cervical spinal cord or used to confirm suspected lesions on sagittal scans. We sought to evaluate the detection rate for MS lesions on axial T2WI scans with full spinal cord coverage in comparison with sagittal scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…The PES scores were higher in NMOSD than in MS patients in this study. Several studies reported 75%-90% of patients with MS showed spinal cord lesions [22][23][24][25]. The percentages are similar to our study.…”
Section: Discussionsupporting
confidence: 91%
“…The PES scores were higher in NMOSD than in MS patients in this study. Several studies reported 75%-90% of patients with MS showed spinal cord lesions [22][23][24][25]. The percentages are similar to our study.…”
Section: Discussionsupporting
confidence: 91%
“…It is estimated that focal spinal cord lesions are present in approximately 50% of PPMS patients [89][90][91]. It is very important to highlight that although in current and very recently published guidelines for diagnosis and monitoring MS patients [92] the sagittal plane is recommended for lesions detection, using additional axial plane more lesions are detected [93,94]. Galler et al [93].…”
Section: Focal T2-weighted Lesionsmentioning
confidence: 99%
“…It is very important to highlight that although in current and very recently published guidelines for diagnosis and monitoring MS patients [92] the sagittal plane is recommended for lesions detection, using additional axial plane more lesions are detected [93,94]. Galler et al [93]. applied axial T2-weighted sequences with full spinal cord.…”
Section: Focal T2-weighted Lesionsmentioning
confidence: 99%
“…For axial imaging, possible sequences are 2D or 3D T2-weighted fast spin-echo sequences. A full cervical cord axial coverage detects more lesions (9–22%) than sagittal scans alone, 11,22 and can also exclude lesions in cases of equivocal abnormalities on sagittal scans. 11,22,23…”
Section: Spinal Cord Lesionsmentioning
confidence: 99%